RESILIENSI FINANSIAL DI TENGAH TURBULENSI GLOBAL: EKSPLORASI MODEL EKONOMI SYARIAH SEBAGAI SOLUSI INSTITUSIONAL - Juhariyah, Juhariyah (LPPM STAI Muhammadiyah Probolinggo, 2025)
The conventional global financial architecture, based on interest (riba) and speculation (gharar), has repeatedly demonstrated its systemic vulnerability in the face of economic turbulence, such as the 2008 crisis and recent geopolitical shocks, exacerbating instability rather than fostering resilience. This study aims to construct an Islamic economics institutional model as an alternative solution that is inherently anti-cyclical and justice-oriented. Using a qualitative approach through conceptual study and theory building, this research analyses normative and empirical literature to synthesize an integrated four-layer model. The findings reveal that financial resilience from an Islamic perspective is built on three main pillars: (1) systemic stability based on the prohibition of riba and gharar, (2) institutionalised distributive justice through zakat and waqf as built-in stabilisers, and (3) connectivity between the financial sector and the real economy. The resulting model encompassing philosophical, integrated macroprudential policy, market instruments, and maqashid-based oversight layers provides an effective operational framework for mitigating liquidity crises, commodity price volatility, and global supply chain disruptions. The study concludes that Islamic economics offers a holistic resilience paradigm and recommends phased implementation through an integrated data platform, halal industrial cluster pilot projects, and advocacy for international standards for broader integration.